2022
DOI: 10.1007/s10741-022-10278-y
|View full text |Cite
|
Sign up to set email alerts
|

Early right ventricular dysfunction after primary percutaneous coronary intervention in anterior versus isolated inferior myocardial infarction assessed by tissue Doppler imaging and speckle tracking echocardiography

Abstract: This study hypothesized that imaging provides information indicating the right ventricular (RV) involvement after anterior or inferior ST-elevation myocardial infarction (STEMI), beyond standard electrocardiogram (ECG) due to the increasing interest in RV function and assessment techniques. This study aimed to compare RV function between anterior and inferior MI without RV involvement using different echocardiographic modalities. This study included 100 patients with anterior (50 patients) and inferior (50 pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…We also also observed that patients with anterior STEMI had lower ejection fraction, and higher infarct area measured by the troponin and CK-MB levels. Similarly, it was reported previous studies that anterior STEMI patients had higher level of cardiac enzymes than non-anterior STEMI patients 5,17,27 . These results suggest that the inflammatory response during myocardial infarction may be related to the infarct location and infarct size, as well as a more widespread inflammation is triggered in anterior STEMI.…”
Section: Discussionsupporting
confidence: 68%
See 3 more Smart Citations
“…We also also observed that patients with anterior STEMI had lower ejection fraction, and higher infarct area measured by the troponin and CK-MB levels. Similarly, it was reported previous studies that anterior STEMI patients had higher level of cardiac enzymes than non-anterior STEMI patients 5,17,27 . These results suggest that the inflammatory response during myocardial infarction may be related to the infarct location and infarct size, as well as a more widespread inflammation is triggered in anterior STEMI.…”
Section: Discussionsupporting
confidence: 68%
“…On the other studies regarding the frequency of 3-vessels between anterior vs. nonanterior STEMI patients are contradictory. Some previous studies found that the 3-vessel disease frequency was higher in non-anterior STEMI 18,19 , whereas others found no significant difference between the two groups 17,20 . In the current study, although the frequency of the 3-vessel disease tended to be higher in non-anterior STEMI (30.8% vs. 21.9%), we observed that this difference did not reach significance.…”
Section: Discussionmentioning
confidence: 78%
See 2 more Smart Citations